CCR5 Antagonist Maraviroc Inhibits Acute Exacerbation of Lung Inflammation Triggered by Influenza Virus in Cigarette Smoke-Exposed Mice - Maximiliano Ruben Ferrero; Cristiana Couto Garcia; Marcella Dutra de Almeida; Jullian Torres Braz da Silva; Daniella Bianchi Reis Insuela; Tatiana Paula Teixeira Ferreira; Diego de Sá Coutinho; Carolina Trindade de Azevedo; Patrícia Machado Rodrigues e Silva; Marco Aurélio Martins (MDPI AG, 2021)
Influenza A virus (IAV) infection is a common cause of acute exacerbations of chronic obstructive pulmonary disease (AECOPD). Since macrophage inflammatory protein 1 α, a chemokine that acts through CC-chemokine receptor (CCR)-5, appears elevated in COPD patients' airways, we evaluated whether CCR5 antagonist Maraviroc could inhibit the exacerbated lung inflammatory response noted after IAV H1N1 infection in mice exposed to cigarette smoke (Cs). C57BL/6 mice, subjected or not to Cs inhalation for 11 days, were infected with H1N1 at day 7. Maraviroc (10 mg/kg) or dexamethasone (1 mg/kg) were given in a therapeutic schedule, followed by the analyses of lung function, survival rate, and inflammatory changes. As compared to mice subjected to Cs or H1N1 alone, the insult combination significantly worsened airway obstruction, neutrophil infiltration in the airways, and the survival rate. All changes were sensitive to Maraviroc but not dexamethasone. Maraviroc also reduced the accumulation of neutrophils and macrophages as well as CXCL1 production in the lung tissue, and serum levels of IL-6, whereas comparable viral titers in the lungs were noted in all infected groups. Collectively, these findings suggest that Maraviroc oral treatment could be an effective therapy for controlling acute exacerbations of respiratory diseases such as COPD.